Steam explosion enhances phenolic profiles and antioxidant activity in mung beans. Issue 4 (22nd February 2022) - Wan, Fachun; Hou, Chunyu; Luo, Kaiyun; Cheng, Anwei
Abstract: Steam explosion (SE), as a physicochemical pretreatment process, has the dual effect of high temperature and high pressure. In this study, SE was applied to pretreat mung beans to increase phenolic extraction and their antioxidant activity. It can make the material loose and porous, which is beneficial to the release of phenolic compounds from mung beans. Insoluble‐bound phenolics (IBPs) were the dominating fraction, followed by glycosidic phenolics (GPs) and esterified phenolics (EPs), and free phenolics (FPs) were the lowest in mung beans. After SE, the maximum contents of FPs, EPs, GPs, IBPs, and total phenolics were detected at 0.75 MPa for 30 s, which were 1.47‐, 1.87‐, 1.73‐, 1.48‐, and 1.58‐fold compared with the untreated samples, respectively. On the whole, the effect of SE on phenolics in mung beans first increased and then decreased. SE increased the contents of protocatechuic acid, p ‐coumaric acid, ferulic acid, catechin, and epicatechin; but there was a decrease in caffeic acid. Compared with the untreated samples, the antioxidant activity of FPs, GPAs, EPs, and IBPs was also improved by SE. The relationship between the phenolic content and antioxidant activity was very high with coefficients of 2, 2′‐azinobis (3‐ethylbenzothiazoline‐6‐ sulfonic acid) > 2, 2′‐diphenyl‐1‐picrylhydrazyl > ferric reducing antioxidant power. In conclusion, an appropriate SE can lead to a more efficient extraction of phenolics and improvement of antioxidant activity in mung beans. Abstract : Steam explosion (SE) formed the large cavities and intercellular spaces of mung beans. SE increased the yields of insoluble‐bound (IBPAs), glycosided (GPAs), esterified (EPAs) and free phenolic acids (FPAs). SE enhanced the antioxidant activity of IBPAs, GPAs, EPAs, FPAs in mung beans.